Hole transport material based on gallium I-III-VI group semiconductor nanoparticles, perovskite solar cell and preparation method of perovskite solar cell
By using hole transport materials of gallium-based I-III-VI semiconductor nanoparticles in perovskite solar cells, the problems of low stability and carrier transmission efficiency of trans perovskite solar cells are solved, and the more High output power and stability.
Patent Information
- Application Number
- CN202410576776.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-10
- Publication Date
- 2025-02-18
AI Technical Summary
Trans perovskite solar cells have stability problems in commercial mass production, especially the low efficiency of photogenerated carrier transmission, the accumulation of carriers between perovskite and charge transport layers and energy loss resulting in output power Reduced, while wide-bandgap perovskite batteries have serious halogen migration and phase segregation problems.
Using hole transport materials based on gallium-based I-III-VI semiconductor nanoparticles, gallium-based I-III-VI semiconductor nanoparticles were synthesized by thermal injection, and their surface ligands were replaced with shorter through ligand replacement method. chain ligands form stable hole transport material for hole transport layers of perovskite solar cells.
The output power and stability of perovskite solar cells are improved, and by optimizing the energy band position and stability of the hole transport layer, the carrier transmission efficiency is improved, interface defects are reduced, and the potential of the battery is enhanced.
Smart Images

Figure CN119461464A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar cells, and in particular to a perovskite solar cell based on a hole transport material of gallium-based I-III-VI group semiconductor nanoparticles and a preparation method thereof. Background Art
[0002] The stability of perovskite solar cells under service conditions is a decisive factor in their commercial large-scale mass production. The structure of inverse perovskite solar cells is suitable for thin-film stacked cells, and their efficiency and stability are particularly important. Compared with the formal structure, inverse perovskite cells have low efficiency and poor stability. The root cause is that the transmission efficiency of photogenerated carriers is low, which leads to the accumulation and recombination of carriers between the perovskite and the charge transfer layer. Energy loss causes the battery output power to decrease. On the other hand, wide-bandgap perovskite top cells for stacked thin-film photovoltaic technology have serious halogen migration and phase segregation problems. The interaction between migrating ions and carriers can produce deep energy level defects at the interface, further reducing the carrier transport efficiency, producing a relaxation effect, and affecting output stability.
[0003] Therefore, it is necessary to provide an inverted perovskite solar cell that can help increase battery output power and enhance battery stability. Summary of the invention
[0004] Based on this, the present invention provides a method for preparing a hole transport material based on gallium-based I-III-VI group semiconductor nanoparticles, and a corresponding structure of a perovskite solar cell.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] The present invention provides a method for preparing a hole transport material based on gallium-based I-III-VI group semiconductor nanoparticles. The method comprises: dissolving a group I element and a group III element in a solvent and a surfactant to obtain a precursor solution containing the group I element and the group III element; preparing a group VI element monomer; synthesizing the precursor solution containing the group I element and the group III element and the group VI element monomer by a hot injection method to obtain gallium-based I-III-VI group semiconductor nanoparticles; replacing the surface ligands of the gallium-based I-III-VI group semiconductor nanoparticles with short chain ligands by a ligand replacement method; The hole transport material based on gallium-based I-III-VI semiconductor nanoparticles is obtained; wherein, in the gallium-based I-III-VI semiconductor nanoparticles, the group I element is one of silver and copper or a mixture, the group III element is gallium, and the group VI element is sulfur; the molar ratio of the group I element to the group III element is 1:2-1:1; the molar ratio of the sum of the group I element and the group III element to the group VI element is 1:4; the group I element is added in the form of a precursor salt of silver chloride and / or cuprous chloride, the group III element is added in the form of gallium chloride, and the group VI element is added in the form of sulfur.
[0007] Furthermore, in the step of dissolving the group I element and the group III element in a solvent and a surfactant to obtain a precursor solution containing the group I element and the group III element, the solvent is oleylamine and the surfactant is n-dodecyl mercaptan; preferably, the molar ratio of oleylamine to the precursor salt of the group I element is 100:1, and the volume ratio of n-dodecyl mercaptan to oleylamine is 2:3.
[0008] Furthermore, the structure of the gallium-based I-III-VI group semiconductor nanoparticles is chalcopyrite-type, round in shape, and has a size between 3nm and 6nm.
[0009] Furthermore, the step of preparing the group VI element monomer is specifically as follows: the group VI element monomer is formed by uniformly mixing sulfur element and oleylamine by ultrasonication; preferably, the ratio of sulfur element to oleylamine is: 2 ml of oleylamine is mixed with every 1 mmol of sulfur powder.
[0010] Furthermore, in the step of synthesizing the precursor solution containing group I elements and group III elements and group VI element monomers by hot injection to obtain gallium-based group I-III-VI semiconductor nanoparticles, the reaction temperature is controlled between 180°C and 190°C, and the reaction time is 4 minutes; the precursor mixed solution obtained after the reaction is washed, centrifuged, and purified once by a mixed solution of n-hexane and ethanol in a volume ratio of 1:2, and dispersed in cyclohexane or toluene to obtain solution A; preferably, a syringe needle with a diameter of 0.8 mm is used to inject the group VI element monomer into the precursor mixed solution.
[0011] Furthermore, the step of replacing the surface ligands of the gallium-based I-III-VI semiconductor nanoparticles with short-chain ligands by a ligand replacement method to obtain the hole transport material based on the gallium-based I-III-VI semiconductor nanoparticles specifically includes: step 1, dissolving the short-chain ligand in a solvent to prepare a short-chain ligand solution B; mixing the solution A and the solution B in a certain proportion to obtain a solution C; step 2, washing, centrifuging, and purifying the solution C 2-3 times with a volume ratio of 1:2 n-hexane and ethanol mixed solution, and dispersing it in n-octane to obtain a solution D; step 3, dissolving the solution D to a concentration of 10 mg / ml-12 mg / ml and placing it in a glove box for standby use, thereby obtaining the hole transport material based on the gallium-based I-III-VI semiconductor nanoparticles; the short-chain ligand includes a halogen compound, and the cation in the halogen compound includes one of lead, zinc, cadmium, or 2-phenylethylamine (PEA + ), methylamine (MA + ) organic molecules; the anions in the halogen compounds include one of iodine and chlorine or a mixture; preferably, the halogen compounds are zinc chloride, lead iodide, phenethylammonium chloride (PEACl), phenethylammonium iodide (PEAI), methylammonium chloride (MACl), methylammonium iodide (MAI), cadmium chloride; wherein, when the short-chain ligand is selected from zinc chloride, the solvent is anhydrous ethanol; when the short-chain ligand is selected from lead iodide or methylammonium iodide or methylammonium chloride, the solvent is a mixed solution of anhydrous ethanol and DMF; wherein, the volume ratio of anhydrous ethanol to DMF is 100:1; when the short-chain ligand is selected from cadmium chloride, the solvent is oleylamine; when the short-chain ligand is selected from phenylammonium iodide or phenylammonium chloride, the solvent is a mixed solution of anhydrous ethanol and DMF; wherein, the ratio of anhydrous ethanol to DMF is 50:1.
[0012] Furthermore, the ligand replacement method is: using a mixed solution of hexane and ethanol in a volume ratio of 1:2 to wash the precursor mixed solution obtained after the reaction, removing the supernatant after centrifugation, and dispersing the precipitate in cyclohexane to obtain solution A; then preparing ligand solution B, dissolving the halogen compound in a mixed solution of ethanol and DMF in a volume ratio of 10:1, reacting at 60°C-80°C for 30 minutes, and obtaining solution C; washing and purifying the solution C twice, centrifuging, removing the supernatant, and dispersing the precipitate in n-octane to obtain solution D.
[0013] The present invention also provides a hole transport material based on gallium-based I-III-VI semiconductor nanoparticles prepared by the above-mentioned method for preparing a hole transport material based on gallium-based I-III-VI semiconductor nanoparticles.
[0014] The present invention further provides a perovskite solar cell, which comprises a substrate, a transparent bottom electrode, a hole functional layer, a perovskite absorption layer, an electron transport layer, and a metal top electrode arranged in sequence from bottom to top; wherein the hole transport layer is made of the hole transport material based on gallium-based I-III-VI group semiconductor nanoparticles as described above; the substrate is a glass substrate; the material of the transparent bottom electrode is indium-doped tin oxide (ITO); the perovskite absorption layer is an organic-inorganic hybrid perovskite material with a bandgap width greater than 1.6 eV; the material of the electron transport layer is C 60 ; The material of the transparent top electrode is silver or gold.
[0015] Furthermore, the thickness of the transparent bottom electrode is 40nm-100nm; the thickness of the hole functional layer is 1nm-20nm; the thickness of the light-emitting layer is 500nm-700nm; the thickness of the electron transport layer is 50nm-100nm; and the thickness of the transparent top electrode is 100nm-150nm.
[0016] Compared with nickel oxide and / or self-assembled small molecule hole transport materials in the prior art, the technical solution provided by the present invention has at least the following advantages:
[0017] 1. In the process of material synthesis, the present invention realizes a hole transport layer with adjustable energy band (specifically adjustable within the range of 4.9eV to 5.8eV) through feed ratio and ligand engineering, and especially designs hole transport materials with low work function for wide bandgap perovskite absorption layer, which helps to improve the conversion efficiency and stability of perovskite-based stacked top cells. However, the nickel oxide in the prior art is combined with self-assembled small molecules, and the adjustable range of energy band position is small.
[0018] 2. The gallium-based I-III-VI nanoparticles used in the present invention form an ionized layer on the surface to stabilize the nanoparticle solution, which is more stable than the nickel oxide solution. The yield is improved in large-area processes.
[0019] 3. The halogen compound short-chain ligands used in the present invention can inhibit ion migration in the perovskite absorption layer, while nickel oxide or self-assembled small molecules do not have this effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] One or more embodiments are exemplarily described by pictures in the corresponding drawings, and these exemplifications do not constitute limitations on the embodiments. Unless otherwise stated, the pictures in the drawings do not constitute proportional limitations.
[0021] Figure 1 This is a schematic diagram of the synthesis process of copper gallium sulfur quantum dots in Example 1;
[0022] Figure 2 This is a schematic diagram of the ligand replacement reaction process of Example 1;
[0023] Figure 3 Transmission electron microscope images of silver copper gallium sulfur quantum dots before and after ligand replacement;
[0024] Figure 4 This is the X-ray diffraction pattern of copper gallium sulfur quantum dots before and after ligand replacement;
[0025] Figure 5 This is a schematic diagram of the overall cross-sectional structure of the perovskite solar cell prepared in Example 1;
[0026] Figure 6 Schematic diagram of the relationship between current density and voltage during the perovskite solar cell of Example 1.
[0027] Description of main figures:
[0028] 1-1 a mixed clear solution of copper, silver and gallium precursors, 1-2 a sulfur precursor solution, 1-3 a gas scrubber, 1-4 a thermocouple, 1-5 a three-necked flask, 1-6 a syringe;
[0029] 2-1 glass sample bottle, 2-2 silver copper gallium sulfur nanoparticle dispersion after crude purification, 2-3 MAI ligand solution, 2-4 mixed solution after reaction;
[0030] 3-1 glass substrate, 3-2 transparent bottom electrode, 3-3 hole functional layer, 3-4 perovskite absorption layer, 3-5 electron transport layer, 3-6 transparent top electrode. DETAILED DESCRIPTION
[0031] Thin-film tandem photovoltaic technology is a new type of portable mobile energy, which has the following advantages: high photoelectric conversion efficiency, good ductility, low cost, roll-to-roll preparation, etc. It has broad application prospects in the fields of building photovoltaic integration, consumer electronics, automotive electronics, etc. In addition, organometallic halide perovskite solar cells have the advantages of long diffusion distance and minority carrier lifetime, adjustable energy band and solution preparation. Wide bandgap perovskite cells are widely used in thin-film tandem solar cell technology. For example, perovskite-perovskite solar cells (Nature, 2023, 620, 994-1000), perovskite-chalcopyrite (CN202311762393.5) tandem solar cells.
[0032] Solving the stability problem of wide bandgap perovskite cells is one of the important tasks for the industrialization of stacked thin-film photovoltaic technology. Stability includes: the stability of the microstructure and composition of the perovskite absorber layer itself, the interfacial charge transfer efficiency between the charge transport layer and the perovskite absorber layer, and the encapsulation of the cell. Among them, the interfacial charge transfer efficiency between the charge transport layer and the perovskite absorber layer is directly related to the formation of deep energy level defects at the interface and the matching of the interface energy band. Optimizing the interlayer energy level of the perovskite absorber layer and the charge transport layer and reducing the interface defect concentration can greatly improve the output stability of the perovskite cell under working conditions. Therefore, it is very important to prepare a charge transport layer with high carrier mobility, adjustable energy level, and a passivated perovskite absorber layer for improving the stability of perovskite cells.
[0033] For the wide-bandgap inverse perovskite cells with superstrate stacked structure top cells, there are serious problems of halogen migration and phase segregation. The interaction between migrating ions and carriers can produce deep energy level defects at the interface, causing energy level mismatch, further reducing the carrier transport efficiency, producing relaxation effects, and affecting output stability.
[0034] At present, the commonly used hole transport materials include: organic polymers (PEDOT, PTAA), metal oxides (nickel oxide, cobalt oxide, molybdenum trioxide), interface self-assembled small molecules (MeO-PACz, etc.) and other polymers as hole transport materials. For example, Huang Jinsong's research group used PTAA to prepare trans-wide bandgap battery efficiency Nature Photnics, 2022, 16, 588-594; Tan Hairen's research group used nickel oxide and naphthocarbazole to self-assemble small molecules Nature Energy, 2022, 7, 708-717; Patent: CN202311417020.4 discloses cobalt oxide, and patent CN202311550308.9 discloses multi-zinc-based oxide hole transport interface materials). However, the open-circuit voltage loss of wide-bandgap cells is still relatively high (~0.4V), which is mainly caused by the low carrier transfer efficiency at the interface between the perovskite absorption layer and the charge transfer layer. In addition, the mixed halogens in the wide-bandgap perovskite material undergo phase segregation under polarization conditions, which greatly affects the stability of the material structure and the working stability of the solar cell device.
[0035] Schemes similar to the present invention include patent CN202011010637.0 copper-based quantum dots and quantum dot light-emitting devices, and the invention content includes the synthesis and ligand exchange process of copper-based quantum dots, and the ligand is an organic ligand including 3-mercaptopropionic acid, octanoic acid, octylamine or hexanethiol.
[0036] The inventors found that in the prior art, high-performance inverse perovskite cells mostly use nickel oxide and / or self-assembled small molecule layers as hole transport layers, but nickel oxide is mostly prepared using nanoparticle ink or sputtering methods. Nanoparticles use deionized water or isopropanol as dispersion liquid, which is easy to agglomerate after being placed for a long time and is not easy to prepare on a large scale. In addition, the energy level position of nickel oxide is fixed and difficult to control. Self-assembled small molecules use carbendazim and pyridine phosphate groups to fix the hydroxyl groups on the surface of the substrate conductive glass, but their water-oxygen stability is still problematic.
[0037] In view of the above problems, the present invention discloses a preparation method of a hole transport material based on gallium-based I-III-VI semiconductor nanoparticles and a corresponding perovskite solar cell. Purpose of the invention: 1. Chalcopyrite-type gallium-based I-III-VI semiconductors have hole conductivity characteristics, and their hole concentration and mobility are directly related to the chemical ratio. Suitable for hole transport layer materials of thin-film optoelectronic devices. 2. Quantum dots have a size effect. By changing the size of quantum dots, the band gap of quantum dot materials can be regulated; at the same time, by replacing the original long-chain organic ligands of quantum dots with short-chain ligands, strong electrical coupling between quantum dots and quantum dots can be achieved, thereby enhancing the conductivity of quantum dot films and improving carrier transport efficiency. 3. The halogen anion ligands used to coat quantum dots and coordinate cations form an ionosphere on the surface of quantum dots, stabilize colloidal quantum dots by electrostatic force, and enhance the stability of the formed hole transport layer. 4. The cations on the surface of quantum dots can stabilize the halogen anions in the perovskite absorption layer, which plays a role in inhibiting the migration of halogen ions and passivating defects.
[0038] The present invention discloses a method for preparing a hole transport material of gallium-based I-III-VI group semiconductor nanoparticles, and a corresponding structure of a perovskite solar cell. In order to better illustrate the technical solution of the invention, an inverted perovskite cell with a band gap of 1.70 eV is used as a specific example to describe the specific implementation scheme of the present invention, and is better illustrated in the form of drawings.
[0039] Example 1
[0040] This embodiment provides a method for preparing a hole transport material based on gallium-based I-III-VI group semiconductor nanoparticles, wherein the hole transport material based on gallium-based I-III-VI group semiconductor nanoparticles is specifically methyl iodide ammonium silver copper gallium sulfur quantum dots, and the preparation method comprises the following steps:
[0041] 1. Preparation of copper gallium sulfur quantum dots, the synthesis method is as follows Figure 1 and Figure 2As shown. Among them, steps 1 and 2 of the preparation process are carried out in a three-necked flask 1-5, the atmosphere in the flask is replaced with an inert gas through a gas washer 1-3, the temperature change is monitored through a thermocouple 1-4, and liquid injection is performed through a syringe 1-6;
[0042] Steps 3 and 4 are carried out in the glass sample bottle 2-1, and the solution 2-3 is mixed with the solution 2-2 to react to obtain a solution 2-4.
[0043] The specific process is as follows:
[0044] Step 1: Take 0.05 mmol of silver chloride, 0.45 mmol of cuprous chloride, and 0.5 mmol of gallium chloride and dissolve them in oleylamine and n-dodecyl mercaptan to obtain a mixture. Heat the mixture until it is clear and transparent to obtain a mixed clear solution 1-1 of copper, silver, and gallium precursors, and keep the solution temperature at 120°C-140°C;
[0045] Step 2: In an inert atmosphere, the temperature of the mixed clarified solution 1-1 of copper, silver and gallium precursors is raised to 180°C-190°C. During the heating process, a sulfur precursor solution 1-2 is prepared, and sulfur powder and oleylamine are ultrasonically mixed at room temperature until clarified to obtain the sulfur precursor solution 1-2.
[0046] Step 3: When the temperature of the mixed clarified solution 1-1 of copper, silver and gallium precursors is completely raised, the sulfur precursor solution 1-2 is quickly injected therein, and the reaction time is 4 minutes. The mixed solution after the reaction is cooled to room temperature in a water bath, washed, centrifuged and purified once, and dispersed in toluene to obtain silver-copper-gallium-sulfur quantum dots before ligand replacement. The transmission electron microscope image of the silver-copper-gallium-sulfur quantum dots before ligand replacement is as follows: Figure 3 Left picture in .
[0047] Step 4: Take 100 microliters of silver copper gallium sulfur quantum dots before ligand replacement and put them in a 4 ml glass sample bottle 2-1 without a lid, put the glass sample bottle 2-1 into a vacuum container, remove excess toluene, obtain solid, weigh, and calibrate the concentration of silver copper gallium sulfur quantum dots before ligand replacement. Constant volume to obtain 1 ml copper gallium sulfur quantum dot solution with a concentration of 40 mg / ml, which is the silver copper gallium sulfur nanoparticle dispersion 2-2 after crude purification, and place it in a glove box for standby use.
[0048] 2. Ligand replacement of quantum dots
[0049] Step 1: prepare a 5 mol / L methylammonium iodide solution by dissolving 397.425 mg of methylammonium iodide in a mixed solution of 500 ul of anhydrous ethanol and 5 ul of dimethylformamide (DMF) in a glass sample bottle and ultrasonicating for 1 hour to obtain MAI ligand solution 2-3.
[0050] Step 2: Take 20 μl of MAI ligand solution 2-3 and add it into the roughly purified silver-copper-gallium-sulfur nanoparticle dispersion 2-2, mix and stir at 80° C. for 30 minutes to obtain a reacted mixed solution 2-4.
[0051] Step 3: The reaction mixed solution 2-4 is washed, centrifuged, and purified 2-3 times with n-hexane: ethanol = 1:2 (volume ratio), dispersed in n-octane, and placed in a glove box for standby use to obtain ligand-substituted silver copper gallium sulfur quantum dots, namely, methyl iodide ammonium silver copper gallium sulfur quantum dots. The transmission electron microscope image of methyl iodide ammonium silver copper gallium sulfur quantum dots is shown in FIG. Figure 3 The X-ray diffraction patterns of copper gallium sulfur quantum dots before and after ligand replacement are shown in the right figure. Figure 4 shown.
[0052] It should be understood that there are many ways to prepare the ligand solution, specifically:
[0053] When the short-chain ligand is selected from zinc chloride, the solvent is anhydrous ethanol.
[0054] When the short-chain ligand is selected from lead iodide, methylammonium iodide or methylammonium chloride, the solvent is a mixed solution of anhydrous ethanol and DMF, with a volume ratio of ethanol:DMF=100:1. It can be dissolved by ultrasound at room temperature.
[0055] When the short-chain ligand is selected from cadmium chloride, the solvent is oleylamine, which can be dissolved by stirring at room temperature.
[0056] When the short-chain ligand is selected from phenylammonium iodide and phenylammonium chloride, the solvent is a mixed solution of anhydrous ethanol and DMF, with a volume ratio of ethanol:DMF=50:1, and it can be dissolved by ultrasound at room temperature.
[0057] 3. The third step is to prepare superstrate structure perovskite solar cells.
[0058] Step 1: Prepare ITO with a thickness of about 40nm-100nm as a transparent bottom electrode 3-2 on the glass substrate 3-1 by magnetron sputtering.
[0059] Step 2: Use deionized water, ethanol, acetone, and isopropanol to clean the glass substrate respectively. The method is: ultrasonic at room temperature for 20 minutes. Then put the glass in an oven and dry it for 1 hour. After the surface liquid evaporates, use plasma to treat the ITO, and transfer the treated glass into a glove box with a nitrogen atmosphere.
[0060] Step 3: Spin-coat the silver-copper-gallium-sulfur quantum dots after ligand replacement prepared in the second step on ITO layer by layer at a rotation speed of 3000 rpm for 30 seconds; place on a heating table after spin coating, anneal at 250°C for 30 minutes to prepare a hole functional layer 3-3 with a thickness of 20nm-50nm.
[0061] Step 4: Spin-coat a perovskite absorption layer 3-4 with a thickness between 300nm and 500nm on the hole functional layer.
[0062] Spin coating was performed for 50 seconds at a speed of 5000 rpm. Anti-solvent was injected with a pipette at 30 seconds. After spin coating, the film was placed on a heating table and annealed at 100°C for 30 minutes.
[0063] The preparation of perovskite solution is as follows: when preparing 5 ml of perovskite solution, first weigh 55 mg-60 mg of PlCl2, 15 mg of MACl, 550 mg-600 mg of PbBr2, 950 mg-1000 mg of FAI, 350 mg-400 mg of CrI, and 2400 mg-2500 mg of PbI2, and then dissolve them with a mixed solution of DMF and DMSO, the ratio of DMF to DMFO is 3:1, shake and stir overnight after dissolution, filter and label when using.
[0064] Step 5: Vapor-deposit an electron transport layer 3-5 with a thickness of 80 nm on the perovskite absorption layer by high vacuum thermal evaporation. The specific material is C 60 .
[0065] Step 6: Using a high vacuum thermal evaporation method, a 100-150nm metal electrode is uniformly evaporated on the electron transport layer by covering the mask as a transparent top electrode 3-6. The electrode material is silver or gold, and the evaporation rate is about 10-30 angstroms / second to obtain a blue light superstrate structure perovskite solar cell, whose structure is as follows Figure 5 shown.
[0066] The schematic diagram of the relationship between the current density and voltage during the perovskite solar cell prepared in Example 1 is as follows: Figure 6 shown.
[0067] From the above preparation process, it can be seen that:
[0068] 1. The present invention selects Lewis base anions that are compatible with the acidity of the cations on the surface of gallium-based nanoparticles as short-chain ligands, and considers the polarity of the ligand solvent and the solvent dissociation strength of the polar solvent for the anions and cations contained in the short-chain ligands. The ligand replacement and the stability of the nanoparticles after replacement are achieved.
[0069] By controlling the molar concentration ratio of the ligand and the nanoparticles, without changing the hole conductivity type, a gallium-based I-III-VI group nanoparticle solution with high hole mobility and hole concentration is achieved through a simple one-step method. The solution has good wettability with the substrate and high film quality.
[0070] During the synthesis process, the conduction band and valence band energy levels of the nanoparticle film can be regulated by changing the feed ratio of group I and group III metals. At the same time, among the group I metal elements, the copper content has a greater influence on the hole mobility of the film.
[0071] During the ligand exchange process, different ligands have different effects on the work function of the film. For example, iodide-based short-chain ligands will increase the work function of the nanoparticle film, while chloride-based short-chain ligands will reduce the work function of the nanoparticle film.
[0072] Gallium-based Group I-III-VI nanoparticle films have high transmittance in the visible light range due to their wider band gap.
[0073] In summary, the present invention provides a transparent nanoparticle film with high hole mobility and controllable energy band position. The controllable band gap can increase the Fermi level splitting of the hole transport layer and the electron transport layer, reduce the valence band mismatch between the wide band gap perovskite absorption layer and the hole transport layer, and improve the transmission efficiency of photogenerated holes at the interface.
[0074] 2. The present invention uses a gallium-based nanoparticle film as a hole transport layer for a perovskite solar cell.
[0075] 3. The metal halide ligands used in the present invention, such as lead iodide, methylammonium iodide, phenethylammonium iodide, etc., have cations (Pb 2+ 、MA + 、PEA + ) are coated on the surface of nanoparticles in the form of ionosphere through electrostatic force, and the prepared nanoparticle solution has good stability. And these cations can stabilize the halogen anions (I - Br - , Cl - )Inhibit halogen migration and phase segregation in the wide-bandgap perovskite absorber layer and reduce the body defect concentration.
[0076] 4. The perovskite solar cell based on the gallium-based nanoparticle hole transport layer film used in the present invention has a perovskite / hole transport layer interface bonded by electrostatic force, which reduces interface defects and improves carrier transport efficiency.
[0077] The hole transport layer prepared by gallium-based I-III-VI group nanoparticles is suitable for both narrow-bandgap tin-based perovskite absorption layers and all-perovskite stacked cells.
[0078] For the narrow bandgap perovskite absorption layer, the VI group element can be selenium. The preparation method is the same as the above technical solution, only the sulfur powder needs to be replaced with selenium powder.
[0079] Those skilled in the art can understand that the above-mentioned embodiments are specific examples for implementing the present application, and in practical applications, various changes can be made to them in form and detail without departing from the spirit and scope of the present application. Any person skilled in the art can make their own changes and modifications without departing from the spirit and scope of the present application, so the scope of protection of the present application shall be based on the scope defined in the claims.
Claims
1. A method for preparing a hole transport material based on gallium-based I-III-VI group semiconductor nanoparticles, characterized in that: The method includes: Dissolving the group I element and the group III element in a solvent and a surfactant to obtain a precursor solution containing the group I element and the group III element; Preparation of Group VI element monomers; The precursor solution containing the group I element and the group III element and the group VI element monomer are synthesized by a hot injection method to obtain gallium-based group I-III-VI semiconductor nanoparticles; The surface ligands of the gallium-based I-III-VI semiconductor nanoparticles are replaced with short-chain ligands by a ligand replacement method to obtain the hole transport material based on the gallium-based I-III-VI semiconductor nanoparticles; Among them, in the gallium-based I-III-VI group semiconductor nanoparticles, the group I element is one of silver or copper or a mixture, the group III element is gallium, and the group VI element is sulfur; the molar ratio of the group I element to the group III element is 1:2-1:1; the molar ratio of the sum of the group I element and the group III element to the group VI element is 1:4; The group I elements are added in the form of precursor salts of silver chloride and / or cuprous chloride, the group III elements are added in the form of gallium chloride, and the group VI elements are added in the form of sulfur.
2. The method for preparing a hole transport material based on gallium-based I-III-VI group semiconductor nanoparticles according to claim 1, characterized in that: In the step of dissolving the group I element and the group III element in a solvent and a surfactant to obtain a precursor solution containing the group I element and the group III element, the solvent is oleylamine and the surfactant is n-dodecyl mercaptan; Preferably, the molar ratio of oleylamine to the precursor salt of the group I element is 100:1, and the volume ratio of n-dodecyl mercaptan to oleylamine is 2:
3.
3. The method for preparing a hole transport material based on gallium-based I-III-VI group semiconductor nanoparticles according to claim 1, characterized in that: The gallium-based I-III-VI semiconductor nanoparticles have a chalcopyrite structure, a round shape, and a size between 3nm and 6nm.
4. The method for preparing a hole transport material based on gallium-based I-III-VI group semiconductor nanoparticles according to claim 1, characterized in that: The step of preparing the group VI element monomer is specifically as follows: the group VI element monomer is uniformly mixed with sulfur element and oleylamine by ultrasonication to form a sulfur monomer; Preferably, the ratio of the sulfur element to oleylamine is: 2 ml of oleylamine is mixed with every 1 mmol of sulfur powder.
5. The method for preparing a hole transport material based on gallium-based I-III-VI group semiconductor nanoparticles according to claim 1, characterized in that: In the step of synthesizing the precursor solution containing group I elements and group III elements and group VI element monomers by hot injection to obtain gallium-based group I-III-VI semiconductor nanoparticles, the reaction temperature is controlled between 180° C. and 190° C., and the reaction time is 4 minutes; the precursor mixed solution obtained after the reaction is washed, centrifuged, and purified once by a mixed solution of n-hexane and ethanol in a volume ratio of 1:2, and dispersed in cyclohexane or toluene to obtain solution A; Preferably, the Group VI element monomer is injected into the precursor mixed solution using a syringe needle with a diameter of 0.8 mm.
6. The method for preparing a hole transport material based on gallium-based I-III-VI group semiconductor nanoparticles according to claim 5, characterized in that: The step of replacing the surface ligands of the gallium-based I-III-VI semiconductor nanoparticles with short-chain ligands by a ligand replacement method to obtain the hole transport material based on the gallium-based I-III-VI semiconductor nanoparticles specifically includes: Step 1: dissolving the short-chain ligand in a solvent to prepare a short-chain ligand solution B; mixing the solution A and the solution B in a certain proportion to obtain a solution C; Step 2: washing, centrifuging, and purifying the solution C 2-3 times with a mixture of n-hexane and ethanol in a volume ratio of 1:2, and dispersing the mixture in n-octane to obtain a solution D; Step 3, dissolving the solution D to a concentration of 10 mg / ml-12 mg / ml and placing it in a glove box for standby use, thereby obtaining the hole transport material based on gallium-based I-III-VI group semiconductor nanoparticles; The short-chain ligand includes a halogen compound, wherein the cation in the halogen compound includes one of lead, zinc, and cadmium, or an organic molecule of 2-phenylethylamine and methylamine; the anion in the halogen compound includes one of iodine and chlorine, or a mixture thereof; Preferably, the halogen compound is zinc chloride, lead iodide, phenethylammonium chloride, phenethylammonium iodide, methylammonium chloride, methylammonium iodide, or cadmium chloride; Wherein, when the short-chain ligand is selected from zinc chloride, the solvent is anhydrous ethanol; When the short-chain ligand is selected from lead iodide, methylammonium iodide or methylammonium chloride, the solvent is a mixed solution of anhydrous ethanol and DMF; wherein the volume ratio of anhydrous ethanol to DMF is 100:1; When the short-chain ligand is selected from cadmium chloride, the solvent is oleylamine; When the short-chain ligand is selected from phenylammonium iodide or phenylammonium chloride, the solvent is a mixed solution of anhydrous ethanol and DMF; wherein the ratio of anhydrous ethanol to DMF is 50:
1.
7. The method for preparing a hole transport material based on gallium-based I-III-VI group semiconductor nanoparticles according to claim 6, characterized in that: The ligand replacement method is: The precursor mixed solution obtained after the reaction is washed with a mixed solution of hexane and ethanol in a volume ratio of 1:2, the supernatant is removed after centrifugation, and the precipitate is dispersed in cyclohexane to obtain a solution A; Then prepare ligand solution B, dissolve the halogen compound in a mixture of ethanol and DMF in a volume ratio of 10:1, react at 60° C.-80° C. for 30 minutes, and obtain solution C; The solution C was washed and purified twice, and after centrifugation, the supernatant was removed, and the precipitate was dispersed in n-octane to obtain a solution D.
8. A hole transport material based on gallium-based I-III-VI semiconductor nanoparticles obtained by the method for preparing a hole transport material based on gallium-based I-III-VI semiconductor nanoparticles according to any one of claims 1 to 7.
9. A perovskite solar cell, characterized in that: The perovskite solar cell comprises a substrate, a transparent bottom electrode, a hole functional layer, a perovskite absorption layer, an electron transport layer, and a metal top electrode arranged in sequence from bottom to top; Wherein, the hole transport layer is made of the hole transport material based on gallium-based I-III-VI group semiconductor nanoparticles as claimed in claim 8; The substrate is a glass substrate; The transparent bottom electrode is made of indium-doped tin oxide; The perovskite absorption layer is an organic-inorganic hybrid perovskite material with a bandgap greater than 1.6 eV; The material of the electron transport layer is C 60 ; The transparent top electrode is made of silver or gold.
10. The perovskite solar cell according to claim 9, characterized in that: The thickness of the transparent bottom electrode is 40nm-100nm; The thickness of the hole functional layer is 1nm-20nm; The thickness of the light-emitting layer is 500nm-700nm; The thickness of the electron transport layer is 50nm-100nm; The thickness of the transparent top electrode is 100nm-150nm.
Citation Information
Patent Citations
Quantum dot light-emitting device and application thereof
CN112117387A
P-type multi-element zinc-based oxide semiconductor hole transport interface thin film material and preparation method and application thereof
CN117337064A
Trans-perovskite solar cell based on cobalt oxide hole transport layer and preparation method and application thereof
CN117500339A
Perovskite and CIGS laminated solar cell and application thereof
CN117529128A